A Triangle Problem 2!

Geometry Level 3

Let a 3 + b 3 + c 3 a + b + c = c 2 \dfrac{a^3 + b^3 + c^3}{a + b + c} = c^2 and α \alpha be the measure of B C A \angle{BCA} in radians.

Find: 0 α f ( x ) f ( α x ) + f ( x ) d x \displaystyle\int_{0}^{\alpha} \dfrac{f(x)}{f(\alpha - x) + f(x)} dx


The answer is 0.5235987755982989.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

From the figure , let's take cos ( α ) = a 2 + b 2 c 2 2 a b \displaystyle \cos(\alpha) = \dfrac{a^2+b^2-c^2}{2ab}

From this 2 a b cos ( α ) a 2 = b 2 c 2 2ab\cos(\alpha)-a^2 =b^2-c^2 and 2 a b cos ( α ) b 2 = a 2 c 2 2ab\cos(\alpha)-b^2= a^2-c^2

Now a 3 + b 3 + c 3 a + b + c = c 2 a ( a 2 c 2 ) + b ( b 2 c 2 ) = 0 \displaystyle \dfrac{a^3+b^3+c^3}{a+b+c} =c^2 \implies a(a^2-c^2) +b(b^2-c^2) = 0 a ( 2 a b cos ( α ) b 2 ) + b ( 2 a b cos ( α ) a 2 ) = 0 2 ( a + b ) cos ( α ) = ( a + b ) \implies a(2ab\cos(\alpha)-b^2 )+b(2ab\cos(\alpha)-a^2) = 0 \implies 2(a+b)\cos(\alpha)= (a+b) cos ( α ) = 1 2 α = π 3 \implies \cos(\alpha)= \dfrac{1}{2} \implies \alpha =\dfrac{π}{3}

Now , generally 0 α f ( x ) f ( α x ) + f ( x ) d x = α 2 \displaystyle\int_0^{\alpha} \dfrac{f(x)}{f(\alpha-x)+f(x)} dx= \dfrac{\alpha}{2}

So here answer is α 2 = π 6 \boxed{\dfrac{\alpha}{2} = \dfrac{π}{6} }

Rocco Dalto
Apr 5, 2021

To prove: a b f ( x ) f ( a + b x ) + f ( x ) d x = b a 2 \displaystyle\int_{a}^{b} \dfrac{f(x)}{f(a + b - x) + f(x)} dx = \dfrac{b - a}{2}

Let I = a b f ( x ) f ( a + b x ) + f ( x ) d x I = \displaystyle\int_{a}^{b} \dfrac{f(x)}{f(a + b - x) + f(x)} dx and u = a + b x u = a + b - x

I = a b f ( a + b u ) f ( u ) + f ( a + b u ) d u \implies I = \displaystyle\int_{a}^{b} \dfrac{f(a + b - u)}{f(u) + f(a + b - u)} du

Since u u is a dummy variable we can replace u u by x x to obtain:

I = a b f ( a + b x ) f ( x ) + f ( a + b x ) d x I = \displaystyle\int_{a}^{b} \dfrac{f(a + b - x)}{f(x) + f(a + b - x)} dx

Adding I = a b f ( x ) f ( a + b x ) + f ( x ) d x I = \displaystyle\int_{a}^{b} \dfrac{f(x)}{f(a + b - x) + f(x)} dx and I = a b f ( a + b x ) f ( x ) + f ( a + b x ) d x I = \displaystyle\int_{a}^{b} \dfrac{f(a + b - x)}{f(x) + f(a + b - x)} dx

2 I = a b d x = b a I = b a 2 \implies 2I = \displaystyle\int_{a}^{b} dx = b - a \implies \boxed{I = \dfrac{b - a}{2}} 0 α f ( x ) f ( α x ) + f ( x ) d x = α 2 \implies \displaystyle\int_{0}^{\alpha} \dfrac{f(x)}{f(\alpha - x) + f(x)} dx = \dfrac{\alpha}{2} .

Let a 3 + b 3 + c 3 a + b + c = c 2 \dfrac{a^3 + b^3 + c^3}{a + b + c} = c^2

Using the law of cosines c 2 = a 2 + b 2 2 a b cos ( α ) \implies c^2 = a^2 + b^2 - 2ab\cos(\alpha) \implies

a 3 + b 3 + c 3 = c 2 ( a + b + c ) = ( a + b + c ) ( a 2 + b 2 2 a b cos ( α ) ) = a^3 + b^3 + c^3 = c^2(a + b + c) = (a + b + c)(a^2 + b^2 - 2ab\cos(\alpha)) =

a 3 + b 3 + a b 2 + b a 2 + c a 2 + c b 2 2 ( a 2 b + a b 2 + a b c ) cos ( α ) ) a^3 + b^3 + ab^2 + ba^2 + ca^2 + cb^2 - 2(a^2b + ab^2 + abc)\cos(\alpha)) \implies

c 3 c ( a 2 + b 2 ) = a b 2 + b a 2 2 ( a 2 b + a b 2 + a b c ) cos ( α ) ) c^3 - c(a^2 + b^2) = ab^2 + ba^2 - 2(a^2b + ab^2 + abc)\cos(\alpha)) \implies

c ( c 2 ( a 2 + b 2 ) ) = a b 2 + b a 2 2 ( a 2 b + a b 2 + a b c ) cos ( α ) c(c^2 - (a^2 + b^2)) = ab^2 + ba^2 - 2(a^2b + ab^2 + abc)\cos(\alpha) \implies

c ( 2 a b cos ( α ) ) = 2 a b c cos ( α ) = a b 2 + b a 2 2 ( a 2 b + a b 2 + a b c ) cos ( α ) c(-2ab\cos(\alpha)) = -2abc\cos(\alpha) = ab^2 + ba^2 - 2(a^2b + ab^2 + abc)\cos(\alpha) \implies

a b 2 + b a 2 2 ( a 2 b + a b 2 ) cos ( α ) = 0 ( a b 2 + b a 2 ) ( 1 2 cos ( α ) ) = 0 ab^2 + ba^2 - 2(a^2b + ab^2)\cos(\alpha) = 0 \implies (ab^2 + ba^2)(1 - 2\cos(\alpha)) = 0 \implies

a b ( a + b ) ( 1 2 cos ( α ) ) = 0 ab(a + b)(1 - 2\cos(\alpha)) = 0 and a > 0 a > 0 and b > 0 1 2 cos ( α ) = 0 b > 0 \implies 1 - 2\cos(\alpha) = 0 \implies

cos ( α ) = 1 2 α = π 3 \cos(\alpha) = \dfrac{1}{2} \implies \alpha = \dfrac{\pi}{3} \implies

0 α f ( x ) f ( α x ) + f ( x ) d x = π 6 0.5235987755982989 \displaystyle\int_{0}^{\alpha} \dfrac{f(x)}{f(\alpha - x) + f(x)} dx = \dfrac{\pi}{6} \approx \boxed{0.5235987755982989} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...